Pengaruh Habits of Mind, Self Efficacy, Dan Pandangan Benar Buddhis Terhadap Berpikir Kritis Siswa Pada Mata Pelajaran Bahasa Mandarin di Sma/Smk Kabupaten Meranti - Pendi, Pendi; Mujiyanto, Mujiyanto; Candra, Alexander (Syntax Corporation, 2025)
Critical thinking skills are a vital component of 21st-century education, particularly in mastering foreign languages such as Mandarin. However, students at Senior and Vocational High Schools in Meranti Regency show a low level of critical thinking, which is suspected to be associated with weak habits of mind and low self-efficacy. This study aims to examine the influence of habits of mind, self-efficacy, and Right View from Buddhist teachings on students’ critical thinking in Mandarin language learning. This study employed a quantitative approach with a correlational design. A total of 150 high school/vocational school students were selected as the research sample using stratified random sampling techniques. The instrument used was a questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression to determine the extent of the influence of the independent variables on the dependent variable, both partially and simultaneously. The results indicate that habits of mind, self-efficacy, and Right View each have a positive and significant partial effect on students’ critical thinking. Simultaneously, these three variables contributed 61.1% to the development of critical thinking skills. These findings highlight the importance of cultivating positive thinking habits and self-belief among students during the Mandarin learning process. Therefore, teachers are encouraged to incorporate strategies that strengthen these aspects to foster students who are both critical and reflective thinkers.